EVALUASI PELAKSANAAN PROGRAM BIMBINGAN KONSELING DI TINGKAT SMK KOTA JAKARTA BARAT - Rihya Syifa Qurrotu Ayuna; Yuevelyn Devina Rahmananda; Nadiyatulhaqi Rasyidah; Maryam Qonita; Aip Badrujaman (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
This study measures the evaluation of guidance and counseling programs at vocational schools in West Jakarta. This research aims to measure the extent of the obstacles faced by guidance and counseling teachers in schools in carrying out evaluations of guidance and counseling service programs in schools. Starting from questionnaires and interviews distributed to Guidance and Counseling teachers in West Jakarta, most felt they experienced obstacles from external parties, including administrative matters, funding, support from school principals, teaching loads in other fields and many more. So, with this research, it is hoped that it can become a reference for what needs to be improved in schools so that guidance and counseling service programs can be implemented well and optimally.